207k views
0 votes
Solve the equation by working backward through the number trick.

Solve the equation by working backward through the number trick.-example-1
User Elmarco
by
5.1k points

1 Answer

6 votes
Answer:

x = 3

Explanations:

The given equation is:


(4(x+3)-6)/(2)=\text{ 9}

Step 1: Cross multiply

4 ( x + 3) - 6 = 9(2)

Step 2: Remove the brackets by expanding the equation

4x + 12 - 6 = 18

4x + 6 = 18

Step 3: Collect like terms

4x = 18 - 6

4x = 12

Step 4: Divide both sides by 4

4x / 4 = 12 / 4

x = 3

User Ranksrejoined
by
5.1k points